Use of functional silos to optimize agency decision making - MacGillivray, C. Ian; Burke, Neil; Smadi, Omar G.; Maze, Thomas H. (Midwest Regional University Transportation Center, 2008)
The purpose of the project was to document how agencies make positive use of functional silos and then efficiently allocate resources across them. Functional silos are considered to be any group of expertise within a transportation organization that focuses on one area of expertise. Often, different functional silos compete for agency resources. Functional silos impact their agency positively by allowing members to accumulate expertise in the area of the silo. On the other hand, silos can have a negative impact on resource allocation. The solution to efficient resource allocation is bridging the silos and making overall decisions that offer the most satisfactory solutions globally. Case studies are presented for the Maryland Department of Transportation, Ohio Department of Transportation, and Florida Department of Transportation.
101 p.
Keywords: Asset management; Case studies; State departments of transportation; Decision making; Resource allocation